Communication about distress and well-being: Epistemic and ethical considerations. (August 2022) - White, Ross G.; Fay, Richard; Chiumento, Anna; Giurgi-Oncu, Catalina; Phipps, Alison
Communication about well-being and distress involves multiple stakeholders, including experts by experience (EBE), researchers, clinical practitioners, interpreters, and translators. Communication can involve a variety of discourses and languages and each of the stakeholders may employ diverging epistemologies to understand and explain experiences. These epistemologies may link to different sources of authority and be articulated using particular linguistic resources. Epistemic injustice can occur when stakeholders, intentionally or unintentionally, fail to recognise the validity of other stakeholders' ways of conceptualising and verbalising their experience of well-being and distress. Language lies at the heart of the risk of epistemic injustice involved in the process of expressing well-being and distress as seen in: 1) the interface between divergent discourses on well-being and distress (e.g., biomedical vs. spiritual); and 2) communications involving multiple linguistic resources, which can be subdivided into multi-language communications involving a) translation of assessment measures, and b) interpreted interactions. Some of the challenges of multi-language communication can be addressed by translators or interpreters who strive for conceptual equivalence. We argue, however, that all stakeholders have an important role as "epistemic brokers" in the languaging of possible epistemological differences. Effective epistemic brokering requires that all stakeholders are reflexively and critically aware of the risks of epistemic injustice inherent in multi-language communication. The article concludes with a set of prompts to help raise stakeholder awareness and reflexivity when engaging in communication about well-being and distress.